2015
DOI: 10.1007/s12079-015-0316-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of homocysteine on adipocyte differentiation and CD36 gene expression in 3T3-L1 adipocytes

Abstract: The aim of this study was to investigate the effects of homocysteine (Hcy), a risk factor for cardiovascular diseases, hypertension, stroke and obesity, on expression of CD36 that regulates uptake of oxidized low-density lipoprotein (Ox-LDL) by adipocytes and differentiation of 3T3-L1 cells to adipocytes. Cell viability was determined using MTT assay, and density of triglycerides were measured with Oil Red O staining. The expression levels of CD36 were analyzed using SYBR green assay by quantitative RT-PCR. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Lp-PLA2 protein levels appeared to be induced at an even earlier time point than mRNA expression. This apparent disparity may have arisen because of the capacity of the adipocyte to influx and digest oxLDL and LDL-cholesterol, releasing fatty acid, cholesterol and Lp-PLA2 [ 39 ]. As such, Lp-PLA2 is transported into the adipocyte bound to apolipoprotein B on LDL-cholesterol, its primary carrier [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lp-PLA2 protein levels appeared to be induced at an even earlier time point than mRNA expression. This apparent disparity may have arisen because of the capacity of the adipocyte to influx and digest oxLDL and LDL-cholesterol, releasing fatty acid, cholesterol and Lp-PLA2 [ 39 ]. As such, Lp-PLA2 is transported into the adipocyte bound to apolipoprotein B on LDL-cholesterol, its primary carrier [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…HHcy is also one of the major contributing factors in obesity. Excess Hcy suppresses preadipocyte differentiation (Mentese et al 2016) and lipolysis in primary adipocytes (Wang et al 2011). Decreased lipolysis in adipocytes results in reduced levels of FFA for energy expenditure and accumulation of triglycerides in adipose tissues.…”
Section: Homocysteine and Obesitymentioning
confidence: 99%
“…We also found reports on pyroptosis and lipid metabolism. High homocysteine (HCY) is a risk factor for obesity, elevated serum cysteine levels have been found in obese patients [ 90 ], and high levels of HCY can cause pyroptosis in the presence and absence of LPS [ 90 ]. Researchers found that NLRP3-related inflammation was activated in the fat pads of leptin-deficient mice and high-fat diet-fed obese mice and that NLRP3-dependent caspase-1 activation in hypertrophic adipocytes may induce obesity and adipocyte death through pyroptosis [ 91 ].…”
Section: Discussionmentioning
confidence: 99%